A Theoretical and Experimental Investigation on Free Vibration Vehavior of a Cantilever Beam with a Breathing Crack - M. Rezaee; H. Fekrmandi (Shock and Vibration)
In this paper the free nonlinear vibration behavior of a cracked cantilever beam is investigated both theoretically and experimentally. For simplicity, the dynamic behavior of a cracked beam vibrating at its first mode is simulated using a simple single degree of freedom lumped parameter system. The time varying stiffness is modeled using a harmonic function. The governing equation of motion is solved by a perturbation method – the method of Multiple Scales.